2010
DOI: 10.1074/jbc.m110.147520
|View full text |Cite
|
Sign up to set email alerts
|

Dyrk1A Phosphorylates p53 and Inhibits Proliferation of Embryonic Neuronal Cells

Abstract: Down syndrome (DS) is associated with many neural defects, including reduced brain size and impaired neuronal proliferation, highly contributing to the mental retardation. Those typical characteristics of DS are closely associated with a specific gene group "Down syndrome critical region" (DSCR) on human chromosome 21. Here we investigated the molecular mechanisms underlying impaired neuronal proliferation in DS and, more specifically, a regulatory role for dual-specificity tyrosine-(Y) phosphorylation-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 53 publications
(47 reference statements)
5
109
1
2
Order By: Relevance
“…Several genes up-regulated by DYRK1A depletion were targets of transcription factors negatively regulated by DYRK1A-mediated phosphorylation [14][15][16], including the nuclear factor of activated T cells (NFAT) targets EGR2 [17] and ID2 [18], and the p53 target BTG2 [19]. Genes down-regulated by DYRK1A depletion were largely inducible genes involved in cellular responses to stimuli and immune system processes ( Supplementary Fig S2B).…”
Section: Dyrk1a Shares Target Genes With Hp1 Proteinsmentioning
confidence: 99%
“…Several genes up-regulated by DYRK1A depletion were targets of transcription factors negatively regulated by DYRK1A-mediated phosphorylation [14][15][16], including the nuclear factor of activated T cells (NFAT) targets EGR2 [17] and ID2 [18], and the p53 target BTG2 [19]. Genes down-regulated by DYRK1A depletion were largely inducible genes involved in cellular responses to stimuli and immune system processes ( Supplementary Fig S2B).…”
Section: Dyrk1a Shares Target Genes With Hp1 Proteinsmentioning
confidence: 99%
“…Similarly, increased S100B levels stimulate p53 nuclear accumulation and inhibit proliferation [30]. DYRK1A has alternatively been shown to phosphorylate p53, impair G1/S phase transition and inhibit proliferation [31]. Finally, many HSA21 genes regulate neurogenesis through their effects on NGF, hedgehog, WNT, Notch and insulin signaling pathways [20].…”
Section: Genetics Mechanisms Underlying Neurogenesis In Dsmentioning
confidence: 99%
“…Nevertheless, the mechanism downstream of the MNB/DYRK1A kinase involved in this regulation remains to be elucidated. It has been recently reported that the overexpression of MNB/DYRK1A inhibits proliferation of neural progenitors derived from human embryonic stem cells (Park et al, 2010) and in the developing mouse cerebral cortex (Yabut et al, 2010) through p53 phosphorylation followed by induction of p53 target genes (e.g. p21 CIP1 ) (Park et al, 2010) and by the nuclear export and degradation of Cyclin D1 (Yabut et al, 2010).…”
Section: Kip1mentioning
confidence: 99%